1995
DOI: 10.1007/bf02109365
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of manganese and copper in pallidum of cirrhotic patients: role in the pathogenesis of hepatic encephalopathy?

Abstract: Concentrations of zinc, copper and manganese were measured by atomic absorption spectrometry in samples of globus pallidus obtained at autopsy from 9 patients with chronic liver disease and an equal number of age-matched controls. Manganese concentrations were significantly increased several fold (p < 0.01) in globus pallidus of liver disease patients accompanied by smaller but significant 2-fold increases of copper. Zinc concentrations, on the other hand, were within normal limits. Increased pallidal manganes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…Our case without occupational history of exposure to Mn showed high level of blood Mn level and T1 hyperintensities in the basal ganglia on MRI. Previous studies 21,22) demonstrated increased Mn concentrations in pallidum of cirrhotic patients, and suggested that increased Mn concentrations are responsible for T1 hyperintensities in the basal ganglia on MRI. Increased blood Mn level and T1 hyperintensities in the globus pallidus are the principal findings shown in manganism in industrial settings.…”
Section: Discussionmentioning
confidence: 96%
“…Our case without occupational history of exposure to Mn showed high level of blood Mn level and T1 hyperintensities in the basal ganglia on MRI. Previous studies 21,22) demonstrated increased Mn concentrations in pallidum of cirrhotic patients, and suggested that increased Mn concentrations are responsible for T1 hyperintensities in the basal ganglia on MRI. Increased blood Mn level and T1 hyperintensities in the globus pallidus are the principal findings shown in manganism in industrial settings.…”
Section: Discussionmentioning
confidence: 96%
“…[64][65][66] Manganese deposition in basal ganglia structures of the brain has been proposed as the cause of T1-weighted magnetic resonance signal hyperintensities 65 and cirrhosisrelated Parkinsonism. 67 Recent reports describe dysfunction of the nigrostriatal dopaminergic neuronal pathway related to manganese toxicity in patients with end-stage liver disease.…”
Section: Manganesementioning
confidence: 99%
“…Increased manganese concentrations have been found in the basal ganglia of patients with HE and good correlation occurs between the MRI abnormalities and the blood manganese levels [65].…”
Section: Alterations In the Blood Brain Barrier (Bbb)mentioning
confidence: 99%